Insertional Mutagenesis by a Hybrid PiggyBac and Sleeping Beauty Transposon in the Rat - Furushima, Kenryo (Genetics Society of America, 2012)
A hybrid piggyBac/Sleeping Beauty transposon-based insertional mutagenesis system that can be mobilized by simple breeding was established in the rat. These transposons were engineered to include gene trap sequences and a tyrosinase (Tyr) pigmentation reporter to rescue the albinism of the genetic background used in the mutagenesis strategy. Single-copy transposon insertions were transposed into the rat genome by co-injection of plasmids carrying the transposon and RNA encoding piggyBac transposase into zygotes. The levels of transgenic Tyr expression were influenced by chromosomal context, leading to transgenic rats with different pigmentation that enabled visual genotyping. Transgenic rats designed to ubiquitously express either piggyBac or Sleeping Beauty transposase were generated by standard zygote injection also on an albino background. Bigenic rats carrying single-copy transposons at known loci and transposase transgenes exhibited coat color mosaicism, indicating somatic transposition. PiggyBac or Sleeping Beauty transposase bigenic rats bred with wild-type albino rats yielded offspring with pigmentation distinct from the initial transposon insertions as a consequence of germline transposition to new loci. The germline transposition frequency for Sleeping Beauty and piggyBac was ∼10% or about one new insertion per litter. Approximately 50% of the insertions occurred in introns. Chimeric transcripts containing endogenous and gene trap sequences were identified in Gabrb1 mutant rats. This mutagenesis system based on simple crosses and visual genotyping can be used to generate a collection of single-gene mutations in the rat.